2018
DOI: 10.1017/ice.2017.305
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effect of a Clostridium difficile Infection Prevention Initiative in Veterans Health Administration Long-Term Care Facilities

Abstract: We evaluated rates of clinically confirmed long-term-care facility-onset Clostridium difficile infections from April 2014 through December 2016 in 132 Veterans Affairs facilities after the implementation of a prevention initiative. The quarterly pooled rate decreased 36.1% from the baseline (P<.0009 for trend) by the end of the analysis period. Infect Control Hosp Epidemiol 2018;39:343-345.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…In 2017, 83.5% of VA facilities used NAAT only. 8 Compared to data presented here, there is an increasing trend in VA facilities to perform 2-step testing for the presence of CDI and to document the finding of the toxin assay as the final result.…”
Section: Discussionmentioning
confidence: 79%
“…In 2017, 83.5% of VA facilities used NAAT only. 8 Compared to data presented here, there is an increasing trend in VA facilities to perform 2-step testing for the presence of CDI and to document the finding of the toxin assay as the final result.…”
Section: Discussionmentioning
confidence: 79%
“…Similar multifacility initiatives focused on preventing CDI have been described elsewhere, but they vary in methodology and results. [19][20][21] However, this study, in line with other multifacility and multicenter initiatives, provides evidence that HAI prevention interventions can be successfully implemented across healthcare systems and settings. [22][23][24] Health departments and networks of healthcare facilities that share patients should consider coordinating similar multifacility approaches to reduce transmission and incidence of CDI and antibiotic-resistant infections in their regions.…”
Section: Discussionmentioning
confidence: 58%
“…Previous published reports describe the effectiveness of C. difficile infection prevention initiatives within the VA hospital. 7,21 Although we found that reporting alone did not decrease CDI rates, ASP and infection control are likely important to formulating a comprehensive plan for controlling CDI.…”
Section: Discussionmentioning
confidence: 83%